Development of a computerised accounting system / Baharum Abdul Majid - Abdul Majid, Baharum (1987)
This study is developed with the intention of highlighting the various roles played by the parties involved in the development of a computerised accounting application. The impact of computers on the finance and accounting operations are profound and as students of Accountancy, it is very essential that they are familiar with the computers. Computerisation has helped accountants to analyse, prepare and interpret report accurately and timely. It has become essential for accountants to be equiped with computer knowledge, especially with regards to computer applications.